Design, development and validation of a workplace cyberbullying measure, the WCM. Issue 4 (1st October 2016) - Farley, Samuel; Coyne, Iain; Axtell, Carolyn; Sprigg, Christine
ABSTRACT: Cyberbullying research is beginning to expand from its roots in the youth context into the organizational realm. However, a lack of psychometrically sound scales that capture the diverse features of technological communication has hindered workplace cyberbullying research. The purpose of this study was to develop a valid and reliable measure to assess cyberbullying across various communication technologies and disparate working populations. Three separate studies, involving a total of 944 respondents from different work settings, were conducted to establish a 17-item workplace cyberbullying measure (the WCM). In Study 1, descriptions of workplace cyberbullying behaviours were collected and converted into measurement items. The factor structure and reliability of the scale were examined during Study 2. Further validation of the WCM was established in Study three by assessing correlations with a wide range of variables. Regression analysis demonstrated that the measure explained significant incremental variance in emotional exhaustion over and above existing harassment constructs. Justification for developing the WCM rather than adapting existing measures is presented, along with implications for research and practice.